Handling Telephone Complaint Calls with Poise: AEC335/CD018, 6/1997 - Telg, Ricky W. (EDIS, 1997)
This fact sheet discussed methods to handle complaint telephone calls. This is an educational guide for people who receive telephone calls and represent the Institute of Food and Agricultural Sciences (IFAS) and the University of Florida.